Finding a new therapeutic approach for no-option Parkinsonisms: mesenchymal stromal cells for progressive supranuclear palsy - Canesi, Margherita (J Transl Med, 2016)
BACKGROUND: The trophic, anti-apoptotic and regenerative effects of bone marrow mesenchymal stromal cells (MSC) may reduce neuronal cell loss in neurodegenerative disorders. METHODS: We used MSC as a novel candidate therapeutic tool in a pilot phase-I study for patients affected by progressive supranuclear palsy (PSP), a rare, severe and no-option form of Parkinsonism. Five patients received the cells by infusion into the cerebral arteries. Effects were assessed using the best available motor function rating scales (UPDRS, Hoehn and Yahr, PSP rating scale), as well as neuropsychological assessments, gait analysis and brain imaging before and after cell administration. RESULTS: One year after cell infusion, all treated patients were alive, except one, who died 9 months after the infusion for reasons not related to cell administration or to disease progression (accidental fall). In all treated patients motor function rating scales remained stable for at least six-months during the one-year follow-up. CONCLUSIONS: We have demonstrated for the first time that MSC administration is feasible in subjects with PSP. In these patients, in whom deterioration of motor function is invariably rapid, we recorded clinical stabilization for at least 6 months. These encouraging results pave the way to the next randomized, placebo-controlled phase-II study that will definitively provide information on the efficacy of this innovative approach. Trial registration ClinicalTrials.gov NCT01824121